Perbuatan Hukum Direksi Mewakili Perseroan Terbatas Dalam Pengikatan Kredit di Bank Dengan Penjaminan Aset Perusahaan - Muawanah Muawanah (Universitas Sriwijaya, 2015)
Abstrak : The Limited Company is called by “Ltd” or in bahasa “PT” as following of right and obligation. The law correlation between PT and Bank result the law correlation is “association”, Moreover the association rule by the book III the Indonesian Civil Code. In the matter to get the credit in Bank, Ltd or “PT” as Debitor in law management is associate credit in Bank, where as a Creditor need approving of commissioner council and The General Meeting of Shareholders to guarantee most of the company asset, as rules in passage 20 the Statute Number 40 in 2007 about Limited Company. The problem in this thesis is How the Commissioner authority stand for Limited Company to associate credit without approving Commissioner council and how is giving approving to director to guarantee Ltd asset which the result more than 50 %. The research used in this thesis is normative research, with analyze a management of law with observing the law subject, such as the research of laws basic, positive law and the law regulation. The result of this thesis is Director has authority stand for Limited Company in associate credit in Bank should the approved by Commissioner council, because the director authority limited by Statute Number 40 in 2007 about Limited Company and Basic of Budget Limited Company. Giving of approving to Director in credit association in the Bank created by 2 (two) ways are decision on The General Meeting of Shareholders and trough by Circulair (Outside Meeting decision), That’s ruled by Passage 9 the Statute number 40 in 2007 about Limited Company. Keywords: Limited Company, Law Management, Law Correlation, Director, Commissioner Council and The General Meeting of Shareholders